급성 일산화탄소 중독 환자에서 응급실 내원 초기 동맥혈 이산화탄소 분압의 임상적 의미 - 양근모; Keun Mo Yang; 전병조; Byeong Jo Chun; 문정미; Jeong Mi Moon; 조용수; Young Soo Cho (대한임상독성학회지, 2019)
Purpose: The objective was to determine the association between PaCO 2 and adverse cardiovascular events (ACVEs) in carbon monoxide (CO)-poisoned patients. Methods: This retrospective study included 194 self-breathing patients after CO poisoning with an indication for hyperbaric oxygen therapy and available arterial blood gas analysis at presentation and 6 hours later. The baseline characteristics and clinical course during hospitalization were collected and compared. The mean PaCO 2 during the first 6 hours after presentation was calculated. Results: The incidence rates of moderate (30 mmHg< PaCO 2 <35 mmHg) or severe (PaCO 2 ≤30 mmHg) hypocapnia at presentation after acute CO poisoning were 40.7% and 26.8%, respectively. The mean PaCO 2 during the first 6 hours was 33 (31-36.7) mmHg. The incidence of ACVEs during hospitalization was 50.5%. A significant linear trend in the incidence of ACVEs was observed across the total ranges of PaCO 2 variables. In multivariate regression analysis, mean PaCO 2 was independently associated with ACVEs (OR 0.798 (95% CI 0.641-0.997)). Conclusion: Mean PaCO 2 during the first 6 hours was associated with increased ACVEs. Given the high incidence of ACVEs and PaCO 2 derangement and the observed association between PaCO 2 and ACVEs, this study suggests that 1) PaCO 2 should be monitored at the acute stage to predict and/or prevent ACVEs; and 2) further study is needed to validate this result and investigate early manipulation of PaCO 2 as treatment.